Perlindungan Hukum Terhadap Narasumber Terkait Konten Berita yang Memuat Informasi Dugaan Tindakan Melawan Hukum - Wesnala, I Made Andika; Budiana, I Nyoman (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 3 (2024)DO - 10.24843/JMHU.2024.v13.i0 3.p06, 2024)
The aim of this research was to analyze the legal protection of sources regarding news content that contains information about alleged unlawful acts. The research method used is a normative research method. The results of the research show that legal protection and the urgency related to ensuring legal protection for sources for information containing alleged unlawful acts are provided and ensured as part of the right or freedom of opinion and freedom of the press so that no one can make efforts to limit or prevent a source. who sees, hears and/or knows important information related to an event that contains information about alleged unlawful acts. Furthermore, based on this, the procedure that can be carried out to anticipate acts of spreading false news or containing elements of pollution can be carried out by reporting to the press council through a request for examination of journalistic works or activities that are suspected of violating the provisions governing the press and/or the Journalistic Code of Ethics.